2011
DOI: 10.1016/j.cellimm.2011.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activity of polyphenols derived from Cassia auriculata flowers in aged rats

Abstract: The immunomodulatory activity of Cassia auriculata (CA)-derived polyphenols was tested on aged rats. Rats (24-26 months old) were given CA polyphenols supplementation at doses of 25, 50, and 100 mg/kg for 28 days. Flow cytometry analysis of CA polyphenols-treated aged rats showed increased T and B cells percentage along with enhanced proliferation of splenocytes in both resting and LPS-stimulated cells. Increased percentage of pan T cells is further supported by an elevation of CD4+, CD8+, and CD4+CD25+ regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 32 publications
2
36
1
2
Order By: Relevance
“…Hence, PolyP exerted immunomodulatory effects, i.e., decreased the level of pro‐inflammatory cytokines with increase in antiinflammatory cytokines. Our observation is in agreement with a previous study by John, Sandrasaigaran, Tong, Adam, & Ramasamy, , who have also shown the immunomodulatory activity of polyphenols derived from Cassia auriculata flowers in aged rats (John et al, ). Furthermore, PolyP significantly curtailed LPS‐induced mRNA expression of iNOS and production of NO.…”
Section: Discussionsupporting
confidence: 94%
“…Hence, PolyP exerted immunomodulatory effects, i.e., decreased the level of pro‐inflammatory cytokines with increase in antiinflammatory cytokines. Our observation is in agreement with a previous study by John, Sandrasaigaran, Tong, Adam, & Ramasamy, , who have also shown the immunomodulatory activity of polyphenols derived from Cassia auriculata flowers in aged rats (John et al, ). Furthermore, PolyP significantly curtailed LPS‐induced mRNA expression of iNOS and production of NO.…”
Section: Discussionsupporting
confidence: 94%
“…In mice receiving oral treatment with polyphenols rich extracts from date palm tree, an increment of the immunocompetent cells, incluinding T helper 1 (Th1), natural killer (NK), macrophages and dendritic cells (DCs) in both Peyer’s patches and spleen [12] was observed. Similar effects were obtained in response to treatment of aged rats with polyphenols from Cassia auriculata , increasing splenic T and B cells [13]. Other studies have been reported mechanisms associated to specific cell groups among the different immune cells modulated by polyphenols.…”
Section: Immune Function and Polyphenolssupporting
confidence: 70%
“…Many studies support the immune modulation actions by polyphenols from diverse sources, describing immune modulator effects on different populations of immune cells [12,13]. In mice receiving oral treatment with polyphenols rich extracts from date palm tree, an increment of the immunocompetent cells, incluinding T helper 1 (Th1), natural killer (NK), macrophages and dendritic cells (DCs) in both Peyer’s patches and spleen [12] was observed.…”
Section: Immune Function and Polyphenolsmentioning
confidence: 99%
“…T cell subsets. This correlates well with the results of Karasawa et al , who observed an incremental increase in the immunocompetent T helper 1 (Th1) cells, NK cells, macrophages and dendritic cells in both Peyer's patches in the gut‐associated lymphoid tissue (GALT) and in germinal centers of the spleen, and John et al , who described an increase in T and B splenic cells in aged rats, both in response to the treatment of experimental animals with polyphenols. Zunino and Storms described an increase in proliferation and immunoglobulin synthesis in B cells in adult individuals treated with pokeweed mitogen (a stimulator of B cells) as a consequence of treatment with resveratrol.…”
Section: Discussionmentioning
confidence: 99%